Productive Zakat Management and Economic Empowerment: Integrating Legal Compliance within Indonesia’s Islamic Social Finance Framework - Muhammad Aziz (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2026)
This study examines the implementation of productive zakat management within Indonesia’s Islamic social finance framework by integrating legal compliance, institutional governance, and economic empowerment perspectives. Despite the significant potential of zakat as a tool for poverty alleviation, its utilization often remains consumptive, limiting its long-term developmental impact. This research aims to analyze how productive zakat is implemented, to evaluate its compliance with Law No. 23 of 2011, and to assess its contribution to the economic empowerment of beneficiaries. A qualitative case study approach was employed, focusing on a local zakat institution in Indonesia. Data were collected through semi-structured interviews, field observations, and document analysis, and were analyzed using thematic analysis combined with a legal compliance framework. The study adopts an integrated theoretical approach, drawing on Islamic social finance, empowerment theory, maqāṣid al-sharī‘ah, and institutional governance perspectives. The findings reveal that productive zakat management has shifted toward empowerment-oriented practices through business capital support, training, and mentoring programs. However, the sustainability of these initiatives depends on the strength of institutional support systems and beneficiary capacity. While the institution demonstrates substantial formal compliance with regulatory requirements, a gap persists between normative compliance and substantive implementation. Furthermore, productive zakat contributes positively to economic empowerment, as evidenced by increased income and business activity among beneficiaries, although long-term resilience remains uneven. This study contributes to the literature by proposing a multi-layered analytical framework that integrates legal compliance with governance and empowerment outcomes in zakat management. It highlights that effective productive zakat requires not only regulatory adherence but also strong institutional capacity and continuous empowerment strategies. The findings offer practical insights for policymakers and zakat institutions to enhance governance mechanisms and optimize the role of zakat as a sustainable development instrument within Islamic social finance.